Depiction of Tyrion Lannister as a Dwarf in Game of Thrones Series - Salim, Surumi; K, Sreena (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT–Disabled people have always been a topic of discussion in media from the early days itself. But they were always portrayed as the weak, jealous, wicked and not-so—good category. Many studies had been done in this concern. Studies have proven that the demonstration in media influence people a lot in their real life. Their attitude towards disabled people were also influenced by main stream media. And alot of those researches suggested a new wave of change to come in main stream media regarding the depiction of disabled. Many television programs and web series are made portraying disabled people in new light. ‘Good Doctor’ television series is a popular example. The leading character Shaun is a surgeon with autism. Game of Thrones has paved a new path in the whole television and web series breaking all the norms and stereotype existed till date in media. The female characters were treated equal to male characters, disabled characters were depicted with equal importance to abled characters, masculinity was a choice, and representation of other gender in good light were the major milestones in the 9 year long television series. Here, the study analyses the representation of one of the main disabled characters of the series: Tyrion Lannister, who is a dwarf. With the support of early studies, the depiction of disabled in powerful way, giving them equal screen space as the other leading characters, and casting a real dwarf man to play the role of Tyrion Lannister has made a change in the attitude of viewers towards disabled people. Other than Simply naming them ‘Differently abled’, people have actually started accepting them so.